PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS POTENSI LOKAL MATERI ASAM BASA DI KELAS XI MIA SMA NEGERI 2 KUPANG - Dre, Stefanus; Wariani, Theresia; Tukan, Maria Benedikta (Jurnal Suluh Pendidikan, 2025)
The aim of this research is to determine the validity of the Student Worksheet (LKPD) based on the local potential of acid-base material, to find out the learning outcomes of students after using the Student Worksheet (LKPD) based on the local potential of acid-base material that was developed, to find out the response of students to the Student Worksheet (LKPD) based on the local potential of acid-base material that was developed. This type of research is research and development (Research & Development). The instruments used in this research were validation sheets, test sheets, and student response questionnaires. The material expert validation results obtained were in the valid category with a percentage of 82%, the media expert validation results obtained were in the very valid category with a percentage of 86%, the student learning outcomes for the knowledge (KI-3) and skills (KI-4) aspects were declared complete with the overall average completeness of learning outcomes obtained from 20 students being 86.3, and the percentage of student responses obtained was 91%.